Architects + engineers = structures - Margolius, Ivan
On a cohesive building design team where the members contribute equally, resulting in unique and exceptional designs. These are architects and engineers who entice beautty into buildings not just with lines on paper and calculations but with intuition, innovation and feeling for the needs of people, materials, strength, proportion, lightness and elegance